2014
DOI: 10.1186/1471-2407-14-649
|View full text |Cite
|
Sign up to set email alerts
|

High serum levels of Dickkopf-1 are associated with a poor prognosis in prostate cancer patients

Abstract: BackgroundThe Wnt inhibitor Dickkopf-1 (DKK-1) has been linked to the progression of malignant bone disease by impairing osteoblast activity. In addition, there is increasing data to suggest direct tumor promoting effects of DKK-1. The prognostic role of DKK-1 expression in prostate cancer remains unclear.MethodsA prostate cancer tissue microarray (n = 400) was stained for DKK-1 and DKK-1 serum levels were measured in 80 patients with prostate cancer. The independent prognostic value of DKK-1 expression was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 16 publications
3
54
0
1
Order By: Relevance
“…This finding may indicate that absence of Wnt pathway inhibition by DKK-1 promotes oncogenesis, an idea supported by previous data showing that modulators of bone turnover can be altered not only in metastatic disease but also during early stages of tumor progression [7,13]. Liang et al also observed lower median DKK-1 level in PC patients compared to controls [14].…”
Section: Disease Markerssupporting
confidence: 55%
See 1 more Smart Citation
“…This finding may indicate that absence of Wnt pathway inhibition by DKK-1 promotes oncogenesis, an idea supported by previous data showing that modulators of bone turnover can be altered not only in metastatic disease but also during early stages of tumor progression [7,13]. Liang et al also observed lower median DKK-1 level in PC patients compared to controls [14].…”
Section: Disease Markerssupporting
confidence: 55%
“…However, this finding failed to meet statistical significance. Data regarding differences of DKK-1 in BPH and PC are scarce and partially discrepant [13]. Our findings, together with the lack of correlation between DKK-1 tissue expression and DKK-1 serum levels, may be explained by the hypothesis that PC tissue-derived DKK-1 only modestly influences systemic serum DKK-1 levels [13].…”
Section: Disease Markersmentioning
confidence: 60%
“…In some cases, the expression of DKK-1 has been shown to be upregulated in various kinds of cancers. Rachner et al (2014) showed that both tissue and serum DKK-1 levels were significantly higher in prostate cancer patients compared with healthy controls. In addition, high serum DKK-1 levels were shown to be an independent prognostic factor for prostate cancer, suggesting that DKK-1 might act as an oncogene in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are numerous molecular markers for the evaluation of the prognosis of prostate cancer, such as auxin, vascular endothelial growth factor, and transforming growth factor beta 1, etc. These provide effective references for the clinical treatment and prognosis of prostate cancer (Rachner et al, 2014).…”
Section: Discussionmentioning
confidence: 99%